Almost Periodicity for a Nonautonomous Discrete Dispersive Population Model. (1st December 2016) - Cuevas, Claudio; Dantas, Filipe; Soto, Herme
ABSTRACT: In this article, study the almost periodic profile of solutions for nonautonomous difference equations in Banach spaces. We apply our results in population dynamics.